Comparison of diagnostic accuracy of the GeneXpert Ultra and cell-free nucleic acid assay for tuberculous meningitis: A multicentre prospective study. (September 2020) - Shao, Lingling; Qiu, Chao; Zheng, Liheng; Yang, Yang; Yang, Xinting; Liang, Qingtao; Zhang, Yun; Che, Nanying; Pang, Yu; Duan, Hongfei
Highlights: A prospective study was conducted to evaluate the performance of Xpert Ultra for diagnosing tuberculosis meningitis (TBM). Xpert Ultra and cell-free DNA (cfDNA) assay showed optimal sensitivity compared with mycobacteria growth indicator tube (MGIT) culture. There was no significant correlation between bacterial load and TBM severity in the participants. Abstract: Design: A prospective multicentre study was conducted to compare the diagnostic accuracy of the GeneXpert MTB/RIF Ultra (Xpert Ultra) and cell-free DNA (cfDNA) assay for tuberculous meningitis (TBM) in China. Methods: A prospective cohort study was conducted among individuals with symptoms suggestive of TBM registered in three TB specialised hospitals in China between June 2018 and January 2019. Results: Overall, 84 patients suggestive of TBM were included in this analysis between June 2018 and January 2019. Using microbiological evidence as reference, the sensitivity/specificity for the diagnostic tests were Xpert Ultra 93.3%/100%, cfDNA 93.3%/92.6% and mycobacteria growth indicator tube (MGIT) culture 13.3%/100%. In addition, the sensitivity of culture was 6.7% when using clinical diagnosis criteria as the gold standard. Xpert Ultra correctly identified 28 cases as TBM, indicating a sensitivity of 46.7%. Notably, four additional TBM cases were detected by cfDNA compared with Xpert Ultra, yielding an overall sensitivity of 53.3%. Statistical analysis revealed that the sensitivity of Xpert Ultra and cfDNA was significantly higher than that of culture. Conclusions: The data demonstrate that Xpert Ultra and cfDNA assay showed optimal sensitivity compared with MGIT culture. In addition, there was no significant correlation between bacterial load and TBM severity in the participants.